La intertextualidad Blanco Amor-Lorca en A Esmorga y La Parranda - DOUCET, Montserrat (Madrygal. Revista de Estudios Gallegos, 2010)
This article tries to highlight the fruitful literary relationship between Eduardo Blanco Amor and Federico García Lorca; for it compares A Esmorga and La Parranda by Blanco Amor and a play by Lorca, Bodas de sangre.